Carotid Artery Stiffness: Imaging Techniques and Impact on Cerebrovascular Disease - Baradaran, Hediyeh; Gupta, Ajay (Frontiers in Cardiovascular Medicine, 2022)
Arterial stiffness is an important measure of vascular aging and atherosclerosis. Though it is measured in many well-known epidemiologic cohort studies, arterial stiffness is often overlooked in routine clinical practice for a number of reasons including difficulties in measurement, variations in definition, and uncertainties surrounding treatment. Central arterial stiffness, a surrogate for aortic stiffness, is the most commonly measured marker of arterial stiffness. In addition to central stiffness, there are also a number of ultrasound based techniques to measure local vascular stiffness, including carotid stiffness. There is evidence that both local carotid stiffness and central arterial stiffness measures are associated with multiple cerebrovascular processes, including stroke and cognitive dysfunction. Mechanistic explanations supporting this association include increased flow load experienced by the cerebral microvasculature leading to cerebral parenchymal damage. In this article, we review definitions of carotid artery stiffness measures and pathophysiologic mechanisms underpinning its association with plaque development and downstream cerebral pathology. We will review the evidence surrounding the association of carotid stiffness measures with downstream manifestations including stroke, cerebral small vessel disease detected on brain MR such as white matter hyperintensities and covert brain infarctions, brain atrophy, and cognitive dysfunction. With consistent definitions, measurement methods, and further scientific support, carotid stiffness may have potential as an imaging-based risk factor for stroke and cognitive decline.